Decreasing prevalence of anaemia in pregnant women at delivery: a quality improvement initiative - Vidushi Kulshrestha; K Aparna Sharma; Neena Malhotra; Anushka Rathi; Swati Sharma; Tanisha Gupta; Aditya Sarkar; Srinidhi Y Reddy; Nambrath Sunita; Joby Titto (BMJ Open Quality)
Anaemia in pregnancy is a critical public health challenge associated with adverse maternal and neonatal outcomes. Despite national programmes and guidelines, India continues to face high anaemia prevalence during pregnancy, with 42.2% in Delhi (National Family Health Survey-5). Addressing gaps in systematic screening, timely diagnosis and effective management is essential to reduce anaemia at delivery and improve maternal health outcomes. At AIIMS, New Delhi, baseline data revealed a 35.57% prevalence of anaemia among booked pregnant women at delivery. Key issues included limited screening, inconsistent management and poor patient adherence to anaemia treatment protocols. This prospective quality improvement (QI) initiative employed the Plan–Do–Study–Act (PDSA) cycle methodology to address anaemia in pregnancy. Interventions focused on systematic screening of women at 30–34 weeks gestation using point-of-care haemoglobin testing (HemoCue), the establishment of a dedicated anaemia management room and the development of standardised operating procedures for diagnosis and management. Weekly team meetings facilitated the identification of challenges and iterative improvements. Sustainability measures, such as structured intern orientation, real-time monitoring through WhatsApp and enhanced team communication, addressed barriers like frequent staff rotations and workflow integration. Over four PDSA cycles, screening coverage reached 95%–100%, with a median anaemia prevalence of 20.04% at delivery, reduced from 35.57% at baseline. Sustained improvements were achieved, with a 3-month median prevalence of 15%. Challenges included integrating workflows and ensuring continuity with rotating staff, mitigated through structured protocols and team reorientation. This QI initiative demonstrates a successful model for reducing anaemia at delivery through systematic screening, effective management and multidisciplinary collaboration. The findings provide a replicable framework for addressing anaemia in resource-limited settings, aligning with national initiatives like the ‘T4 Anemia Room’ concept.